2020
DOI: 10.1002/bmc.5039
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of astilbin, neoastilbin and isoastilbin on human cytochrome CYP3A4 and 2D6 activities

Abstract: Astilbin, neoastilbin and isoastilbin are three flavonoid isomers from Smilacis glabrae Roxb. (S. glabrae). Several studies have shown that consumption of flavonoids can increase the risk of food/drug–drug interaction by affecting the activities of human cytochrome CYP3A4 and 2D6. In the present study, an ultrahigh‐performance liquid chromatography and triple quadrupole mass spectrometry method was developed for the determination of the interaction between three flavonoid isomers and two CYPs. Under the optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to multiple spectroscopic coupled with molecular docking analysis, astilbin has strong binding ability to human CYP2D6 ( Tao et al, 2021 ). Ultrahigh-performance liquid chromatography and triple quadrupole mass spectrometry have been used to confirm the interaction of human CYP3A4 and CYP2D6 with astilbin ( Shi et al, 2021 ). In the present study, astilbin efficiently stimulated the ROS of human CD4 + T cells, indicating the inhibition of CYP3A4 and CYP2D6 by astilbin.…”
Section: Discussionmentioning
confidence: 99%
“…According to multiple spectroscopic coupled with molecular docking analysis, astilbin has strong binding ability to human CYP2D6 ( Tao et al, 2021 ). Ultrahigh-performance liquid chromatography and triple quadrupole mass spectrometry have been used to confirm the interaction of human CYP3A4 and CYP2D6 with astilbin ( Shi et al, 2021 ). In the present study, astilbin efficiently stimulated the ROS of human CD4 + T cells, indicating the inhibition of CYP3A4 and CYP2D6 by astilbin.…”
Section: Discussionmentioning
confidence: 99%
“…Radical scavening(%) = A control − A sample /A sample × 100 (10) where A control is the absorbance of DPPH alone and A sample is the absorbance of DPPH with astilbin in the presence or absence of HSA.…”
Section: Effect Of Hsa On the Antioxidant Capacity Of Astilbinmentioning
confidence: 99%
“…Noteworthily, wines contain high levels of astilbin [ 7 ], which has been shown to contribute notably to the sweet taste of dry wines [ 8 ]. Modern pharmacological studies have shown that astilbin has various pharmacological activities such as anti-inflammatory [ 9 ], immunosuppressive [ 10 ], antioxidant [ 11 ], anti-diabetic [ 12 ] and cardiovascular protection [ 13 ]. Overall observations from data suggested that astilbin is a promising compound and a “star material” for the development of new health food products.…”
Section: Introductionmentioning
confidence: 99%